Atractylmacrols A-E, sesquiterpenes from the rhizomes of Atractylodes macrocephala. (February 2018) - Wang, Shuang-Yan; Ding, Lin-Fen; Su, Jia; Peng, Li-Yan; Song, Liu-Dong; Wu, Xing-De
Graphical abstract: Highlights: Five new sesquiterpenes were isolated from rhizomes of Atractylodes macrocephala . Six known eudesmane sesquiterpenes were isolated. Structures of new compounds were determined by NMR and HRMS methods. Abstract: Phytochemical investigation of the rhizomes of Atractylodes macrocephala led to the isolation of five new sesquiterpenes, atractylmacrols A-E (1-5 ), as well as six known eudesmane sesquiterpenes (6 -11 ). The structures of1 -5 were determined through interpretation of their 1D and 2D NMR spectroscopic data, as well as HREIMS values. Compounds1-5 were evaluated for their inhibitory effects on LPS-induced nitric oxide (NO) production in RAW264.7 macrophages.